Mathematics Lecturers' Views on the Student Experience of Emergency Remote Teaching Due to COVID-19 - Eabhnat Ní Fhloinn; Olivia Fitzmaurice (MDPI AG, 2022)
Due to the COVID-19 pandemic, university closures were commonplace worldwide from March 2020, meaning that lecturers and students had to adapt to emergency remote teaching with little or no notice. In this paper, we report upon the results of an online survey undertaken with university mathematics lecturers during May-June 2020. There were 257 respondents from 29 countries who gave their reactions to emergency remote teaching due to the COVID-19 pandemic. Here, we focus upon lecturers' perceptions of how their students coped with this style of teaching, considering any particular difficulties they reported to their lecturers, their attendance at online teaching sessions, and their engagement in a general way. Lecturers reported students struggling with both hardware and software issues, particularly in relation to fast, reliable broadband. Childcare issues also emerged as a challenge for students during this timeframe, as well as students' personal circumstances in terms of living situations and financial stability. Overall, lecturers reported lower levels of engagement with online learning compared to in-person lectures, which occurred prior to the pandemic. However, four-fifths of respondents were still in regular contact with their students during this time. Many of the studies exploring the impact of COVID-19 on the teaching and learning of mathematics in higher education are small-scale, sometimes single-module studies. Restrictions differed greatly between countries, and indeed between regions, meaning that the results of any regional study cannot be generalised to a more international experience. In addition, the experience of students studying mathematics as their degree programme differed from those who undertook only one mathematics module as part of a science, engineering, or business degree. This paper provides a more global insight into the student experience during the COVID-19 pandemic. By focusing on lecturers, rather than asking students directly, the experiences of those students who may not have engaged with such a study have been included; oftentimes, these students were those who struggled the most with this new format of learning.